International Baccalaureatte Learner Profile: Bringing a Positive Vibe to Global Citizenship - Kamaruddin, Miftahuljanah; Mohd Matore, Mohd Effendi Ewan (International Journal of Psychosocial Rehabilitation, 2020)
The United Nations 2030 Agenda for Sustainable Development Goals (SDG) was launched in 2015 in order to achieve sustainable development due to globalization impact. The changing of global context in term of workforce skills demands education to emphasis on both cognitive and non-cognitive aspects of learning. Thus, the role of education in promoting sustainable development was captured by SDG 4: “Ensure inclusive and equitable quality education and promote lifelong learning opportunities for all” and its corresponding targets. Specifically, Target 4.7 in SDG 4 urges countries to transform education by integrating values based learning in shaping students not only to be responsible citizens but play active role as global citizens. Malaysia has long been concerned in integrating values based learning through education which captured in the National Philosophy of Education and National Curriculum. However, the implementation of values based learning has been daunted by various challenges. The implementation of International Baccalaureate Middle Years Programme among secondary school students of International Baccalaureate World School, Ministry of Education has succeeded in developing International Baccalaureate (IB) Learning Profile, thus, simultaneously inculcate and affirm students to be active global citizens. This study has implication on curriculum reformation and implementation of teaching and learning in schools.